The names of pop groups in the UK hit parades of the 1960s: Patterns and peculiarities. (17th December 2018) - Coffey, Stephen
Abstract : This article discusses the names of pop groups active in the 1960s, specifically those groups who had at least one record in the UK charts. By consulting data on the website of the Londonbased Official Charts Company, a database was compiled of just over 300 group names. The vast majority of the groups were either from the British Isles or North America. The present study reports on aspects of the form and meaning of the names. With regard to form, data is presented regarding the overall structure of names, abbreviated forms, and the use of linguistic features such as ready-made phrases, alliteration, rhyme and wordplay. With regard to meaning, a list of recurring meanings are presented and exemplified. The article also gives examples of how specific reasons or circumstances can contribute to the choice of names, and illustrates the difficulties in documenting this aspect of the naming process.